Constructing porous channels in superhydrophilic polyethersulfone composite nanofibrous membranes for sustainably enhanced photocatalytic activities in wastewater remediation. (29th September 2021) - Chen, Shifan; Guo, Yetong; Yuan, Dandan; He, Chao; Bao, Jianxu; Ai, Sanjiang; Li, Fang; Zhao, Weifeng; Xu, Yuanting; Zhao, Changsheng
Abstract: Photocatalysis is regarded as one of the most promising technologies to remediate wastewater for environmental friendliness. However, most of the powder photocatalysts still suffer from poor hydrophilicity, easy aggregation and difficult recycling, which have restricted their further applications in wastewater treatment. In this study, we constructed porous and superhydrophilic composite polyethersulfone nanofibrous membranes to load titanium dioxide (TiO2 ) and graphitic carbon nitride (g-C3 N4 ) photocatalysts to achieve the UV light and visible light driven photocatalytic degradation for organic contaminants, respectively. Particularly, the resultant mesopores in nanofibers could promote the diffusion of contaminant molecules, facilitate the exposure of photocatalytic active sites, improve the light absorption, and finally enhance the photocatalytic activities. Moreover, benefiting from the further removal of poly(vinylpyrrolidone) during the repetitive reuse process, it was provided with a sustainable enhancement of reusability for the composite nanofibrous membrane, which was superior to most of the traditional wastewater remediation materials. Overall, these encouraging features of porous and superhydrophilic composite nanofibrous membrane not only make it promising candidate for wastewater purification, but also offer new pathways to develop advanced nanofibrous materials for diverse catalysis, adsorption and separation applications in environment remediation. Graphical abstract: Image 1 Highlights: Porous and superhydrophilic polyethersulfone composite nanofibrous membranes were designed. TiO2 and g-C3 N4 were embedded inside the composite nanofibrous membranes to achieve the ultraviolet light and visible light driven photocatalytic degradation for organic pollutants. The numerous mesopores in nanofibers could make photocatalysts accessible, promote light absorption and enhance photocatalytic activity. The superhydrophilicity facilitated the contacts of contaminants and membranes in wastewater remediation. A sustainable enhancement of reusability was achieved during the repetitive reuse process.